"Ebooks for the Classroom+" at University of South Florida Libraries: A Case Study of Database Management. Issue 2 (3rd April 2019) - Mi, Xiying; Pollock, Bonita M.
Abstract: The University of South Florida Libraries has supported a campus-wide "Textbook Affordability Project" initiative by creating and maintaining an ebooks database called "Ebooks for the Classroom+." This database facilitates faculty members' adoption of ebooks as textbooks through library acquisitions in the hope that students can achieve academic success without paying for expensive textbooks. It is built and run by the library, using data based on vendor-supplied information. This paper discusses the approaches, the challenges, and the future plans for building and updating the database.